A Retrospective Review of Physician Assistant Education Association End of Rotation Examinations. Issue 3 (September 2018) - Rizzolo, Denise; Cavanagh, Kimberly; Ziegler, Olivia; Dallas, Andrew D.; Goodman, Joshua; Yunker, Emily
Abstract : Abstract: The PAEA End of Rotation™ exams were developed to assess medical knowledge of the 7 core supervised clinical practice experiences, including Emergency Medicine, Family Medicine, Internal Medicine, General Surgery, Pediatrics, Women's Health, and Psychiatry and Behavioral Health. The examinations were created by experienced PA educators and national exam experts with continual review and content updates. This paper summarizes changes since the inception of the exam program, including test construction and development, reliability, validity, and scale scoring. They are built using content blueprints and topic lists that were developed by experienced PA educators and national examination experts. All examination items are peer reviewed by PA educators and statistically validated for accuracy and consistency by psychometricians who specialize in examination development. This article will review the changes since the inception of the exam program including test construction and development, reliability, validity and scale scoring. Also addressed is an update on the PAEA End of Curriculum™ examination.